A Label-Free Liquid Chromatography–Tandem Mass Spectrometry Method for the Quantitative Analysis of Exosome Pharmacokinetics In Vivo - Bingxuan Li; Fei Yu (Pharmaceutics, 2025)
Background: Exosomes are nanoscale extracellular vesicles actively secreted by cells that play critical roles in disease biomarker discovery, drug delivery, and direct therapeutic applications. However, in vivo pharmacokinetic (PK) studies of exosomes remain limited, hindering their clinical translation. Due to their complex and heterogeneous composition, most existing PK methods rely on chemical or genetic labeling, which may alter their native behavior and complicate accurate analysis. Methods: To address this challenge, we developed a label-free liquid chromatography–tandem mass spectrometry (LC-MS/MS) method to investigate the PK of naive exosome-based therapeutic modalities. Exosomes were isolated from rat plasma using size exclusion chromatography (SEC) and quantified using multiple reaction monitoring (MRM) targeting specific exosomal peptides as surrogate analytes. Following intravenous administration of exosomes via the tail vein, plasma concentrations were determined by peptide peak areas, and PK parameters were calculated using a non-compartmental model. Results: The method was rigorously validated for specificity, linearity, sensitivity, and reproducibility. Its feasibility was further confirmed by successfully characterizing the PK profile of HEK 293F-derived exosomes in rats. Conclusions: This analytical strategy enables direct, label-free quantification of exosomes in plasma and provides a robust platform for advancing exosome-based drug development and translational research.